Agroecological Approaches to Agricultural Development - Pretty, Jules (World Bank, Washington, DC, 2012)
Systems high in sustainability are those that aim to make the best use of environmental goods and services while not damaging these assets. The overarching priority for development assistance agencies should be to incorporate emerging ideas about agricultural sustainability into policies toward recipient countries so that sustainability is at the centre of rather than at the edge of policy. They should take a regional approach emphasizing structural reforms and support; develop partnerships and use participatory approaches with implementing and policy NGOs, CGIAR institutes and national research and extension systems, the private sector, and policy-making departments; ensure that policy making has good monitoring and lesson-learning systems; integrate the concept of agricultural sustainability into poverty reduction strategies and policies; provide long-term support; and increase support for research.